Invasive potential of Borrelia burgdorferi sensu stricto ospC type L strains increases the possible disease risk to humans in the regions of their distribution - Golovchenko, Maryna (Parasit Vectors, 2014)
BACKGROUND: Analysis of Borrelia burgdorferi ospC types from the southeastern U.S.A. supported the common belief that various ospC types are geographically restricted and host specific. Being widely distributed in the region, the southeastern population of B. burgdorferi is represented by a surprisingly small number of ospC types. Types B, G and H are dominant or common and are invasive, while scarce type L, restricted mostly to the southeastern U.S.A., is believed to rarely if ever cause human Lyme disease. OspC type B and L strains are represented in the region at the same rate, however their distribution among tick vectors and vertebrate hosts is unequal. FINDINGS: Direct diagnostics was used to analyze the ability of B. burgdorferi ospC type L strains to disseminate into host tissues. Mice were infected by subcutaneous injections of B. burgdorferi strains of various ospC types with different invasive capability. Spirochete levels were examined in ear, heart, bladder and joint tissues. Noninfected I. ricinus larvae were fed on infected mice until repletion. Infection rates were determined in molted nymphs. Infected nymphs were then fed on naïve mice, and spirochete transmission from infected nymphs to mice was confirmed. CONCLUSIONS: B. burgdorferi ospC type L strains from the southeastern U.S.A. have comparable potential to disseminate into host tissues as ospC types strains commonly associated with human Lyme disease in endemic European and North American regions. We found no difference in the invasive ability of ospC type B and L strains originated either from tick vectors or vertebrate hosts.